Synthesis and Antimicrobial Evaluation of Etodolac-Based Derivatives - Sarah Sattar Mohammed; Muthanna Saadi Farhan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Etodolac, a non-steroidal anti-inflammatory drug (NSAID) with selective cyclo-oxygenase 2 inhibition, is known for its anti-inflammatory properties and reduced gastrointestinal side effects. Recent studies have highlighted its potential for modification to develop derivatives with antimicrobial activity. This study aimed to synthesize and evaluate etodolac derivatives for enhanced antimicrobial efficacy. Specific chemical modifications were introduced to the etodolac structure to investigate their inhibitory effects on medically relevant bacterial and fungal strains. The findings suggest that these derivatives exhibit promising antimicrobial properties, offering potential as alternative therapeutic agents in addressing antimicrobial resistance.